Paulo Freire's Humanist Education in the Perspective of Islamic Education - Simona, Rian; Arsyad, Fahmi (Universitas Sang Bumi Ruwa Jurai, 2025)
This research aims to find out the concept of humanist education according to Paulo Freire and to examine Paulo Freire's thoughts from the perspective of Islamic education. The type of research used in this study is library research, which specifically examines a problem to obtain data for research. The data sources in this study were obtained from primary data (main) and secondary data (supporting or supporting primary data). The approach used in this study is historical-philosophical. Furthermore, the data analysis method used in this study is documentary analysis. The data analysis technique used in this study is content analysis. From the results of the study, it is known that Paulo Freire's educational thoughts contain humanism, academic goals, and the concept of humanist education, which contains the values of Freedom, equality, justice, and deliberation. The results of the analysis of Paulo Freire's humanist education in the perspective of Islamic education are that both have their characteristics but there are some similarities between Paulo Freire's humanist education concept and the concept of education in Islam, while Paulo Freire's humanist education that is by Islamic education is in terms of humanism and human nature. As human nature requires the values of Freedom, equality, justice, and deliberation.